Immunological studies on BaH1 and BaP1, two hemorrhagic metalloproteinases from the venom of the snake Bothrops asper - Rucavado Romero, Alexandra (1995)
No immunological cross-reactivity was observed between BaH1 and BaP1, two hemorrhagic metalloproteinases isolated from B. asper venom, by gel immunodiffusion, Western blotting and neutralization studies. Cross-reactivity was detected with antisera against these toxins in several crotaline and viperine snake venoms by ELISA, whereas no reactivity was observed with either antiserum against the venoms of Bothrops nummifer, Crotalus durissus terrificus, Vipera russelli and several elapid venoms. Antiserum against native BaH1 neutralized hemorrhagic activity of the venoms of B. asper, B. atrox, B. jararaca, Crotalus atrox, C. durissus durissus, Echis carinatus and Trimeresurus flavoviridis, being ineffective against the venoms of Agkistrodon bilineatus and Lachesis muta.